Isolation, screening and induction of mutation in strain for extra cellular lignin peroxidase producing bacteria from soil and its partial purification - Renugadevi R; MP, Ayyappadas; PH, Preethy; S, Savetha (Journal of Research in Biology, 2011)
The Lignin peroxidase enzyme production was carried out through bacteria isolated from sample soil collected around decayed wood at Sulur, Coimbatore. In this report, a mutant of Bacillus subtilis LPTK was obtained after chemical mutagenesis with EMS and screened for better Lignin peroxidase production. In the production optimization studies, the bacterial strain needs temperature around 37OC, pH.6, lactose as a carbon source, peptone as nitrogen source and incubation time for 36 hours for its higher enzyme productivity. The partial purification was also done